Stereoselective synthesis of 1, 3-disubstituted dihydroisoquinolines vial-phenylalanine-derived dihydroisoquinoline N-oxides. Issue 38 (19th September 2018) - Flores-Ferrándiz, Jesús; Carter, Nicholas; González-Soria, Maria José; Wasinska, Malgorzata; Gill, Daniel; Maciá, Beatriz; Caprio, Vittorio
Abstract : Addition of Grignard reagents and alkenes to readily available ( S )-3-(hydroxymethyl)-3, 4-dihydroisoquinoline-2-oxide allow the highly stereoselective synthesis of a range of 1, 3-disubstituted tetrahydroisoquinolines. Abstract : The preparation of chiral pool-derived nitrone3 and its use in the protecting-group free, stereoselective synthesis of a range of 1, 3-disubstituted tetrahydroisoquinolines is described. Grignard reagent additions to nitrone3 yielded trans -1, 3-disubstituted N -hydroxytetrahydroisoquinolines6 with good levels of selectivity, while 1, 3-dipolar cycloadditions to this nitrone provided access to 3-(2-hydroxyalkyl)isoquinolines12 as single diastereomers.